2017
DOI: 10.21608/jssae.2017.37078
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Soil Salinity and Evaluation of Water Quality in Siwa Oasis Using GIS

Abstract: Siwa Oasis represents a promising area for agricultural expansion projects in the western desert of Egypt due to the availability of water resources. However, these areas are suffering from land degradation problems, especially soil salinity. Accordingly, the main objectives of this work were to evaluate and map soil salinity as well as groundwater quality in Siwa Oasis. Therefore, twenty representative soil profiles were randomly distributed throughout the studied area. These profiles were sampled based on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…The fungal strains used in the present study were isolated from Siwa Oasis (soil and water), and from a salt lakes (water and sludge), Egypt. According to Elnaggar et al [11], the salinity of Siwa soil was EC=77 dS m -1 (and ESP=14.62 in average). Samples were collected in sterile containers, transferred to the lab within 24 h and stored at 4º C. They were identified at Assiut University Mycological Center, Accession No AUMC 3200-3221.Mineral salt yeast extract medium (MSY) [12], and Malt extract agar [13] were used for isolation and degradation experiments.…”
Section: Microorganismsmentioning
confidence: 97%
“…The fungal strains used in the present study were isolated from Siwa Oasis (soil and water), and from a salt lakes (water and sludge), Egypt. According to Elnaggar et al [11], the salinity of Siwa soil was EC=77 dS m -1 (and ESP=14.62 in average). Samples were collected in sterile containers, transferred to the lab within 24 h and stored at 4º C. They were identified at Assiut University Mycological Center, Accession No AUMC 3200-3221.Mineral salt yeast extract medium (MSY) [12], and Malt extract agar [13] were used for isolation and degradation experiments.…”
Section: Microorganismsmentioning
confidence: 97%
“…Water logging and consequentially salinization are the major land degradation problems especially under the arid and semi-arid climates (Dwivedi et al, 1999;Elnaggar et al, 2017). El- Baroudy and Moghanm (2014) found that the productivity of more than 70% of soils in the middle part of the Nile-Delta was declined due to the improper land management practices.…”
Section: Introductionmentioning
confidence: 99%
“…It is the largest oasis among the Egyptian oases, which is located about 530 kilometers west of the Nile valley and 250 kilometers south of the Mediterranean Sea. It represents a promising area for land reclamation and agriculture expansion in the western desert of Egypt due to the availability of water resources (Elnaggar et al 2017). At the same time, environmental problems, such as waterlogging and soil salinization, are major challenges that undermine sustainable land management and consequently agriculture sustainability in Siwa oasis, where agriculture represents the basis of Siwa economy (IUCN 2000;Al-Kadi 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Several authors have documented these environmental problems and their negative impact on the agricultural land of the oasis (AbdelRahman et al 2019; Aly 2019;Elnaggar et al 2017;Rashed 2016;Abdul Ghafar 2014;Masoud and Koike 2006). Generally, waterlogging problems can be classified as natural, quasinatural and anthropogenic based on their origin and they may be permanent or seasonal based on time scale (Sahu 2018).…”
Section: Introductionmentioning
confidence: 99%